Skin Tissue Engineering: Application of Adipose-Derived Stem Cells. (27th February 2017) - Klar, Agnes S.; Zimoch, Jakub; Biedermann, Thomas
Abstract : Perception of the adipose tissue has changed dramatically over the last few decades. Identification of adipose-derived stem cells (ASCs) ultimately transformed paradigm of this tissue from a passive energy depot into a promising stem cell source with properties of self-renewal and multipotential differentiation. As compared to bone marrow-derived stem cells (BMSCs), ASCs are more easily accessible and their isolation yields higher amount of stem cells. Therefore, the ASCs are of high interest for stem cell-based therapies and skin tissue engineering. Currently, freshly isolated stromal vascular fraction (SVF), which may be used directly without any expansion, was also assessed to be highly effective in treating skin radiation injuries, burns, or nonhealing wounds such as diabetic ulcers. In this paper, we review the characteristics of SVF and ASCs and the efficacy of their treatment for skin injuries and disorders.